Bologna Healing Stifle Injury Index: A Comparison of Three Surgical Techniques for the Treatment of Cranial Cruciate Ligament Rupture in Dogs - Pinna, Stefania; Lanzi, Francesco; Grassato, Lisa (Frontiers in Veterinary Science, 2020)
The aim of this retrospective study was to test the efficacy of the Bologna Healing Stifle Injury Index (BHSII) in assessing the medium-term outcomes of dogs treated for cranial cruciate ligament rupture. This tool can be used for comparison across surgical interventions. The study population included 53 dogs with unilateral cranial cruciate ligament rupture treated using either Paatsama, Tight-Rope or tibial tuberosity advancement techniques, and 20 orthopedically sound dogs for comparative purposes. The BHSII was utilized for all the treated dogs at the time of surgery, and 1, 3 and 6 months postoperatively, while it was utilized twice in the control group. Although all the techniques achieved a successful outcome at the end of the evaluation, the application of the BHSII permitted differentiating results at each time point and stimulating discussion regarding the rapidity and degree of the healing process for each technique. It also pointed out some incongruities between the owner’s and the clinician’s assessment of the process. These achievements demonstrated that the BHSII should be considered by the research and clinical communities as an effective and easy tool which can be used as a repeatable and standardized method of comparison of the progress at different time points towards a final good outcome in dogs treated for cranial cruciate ligament rupture.